The influence of chemical composition of LNG on the supercritical heat transfer in an intermediate fluid vaporizer. (April 2018) - Xu, Shuangqing; Chen, Xuedong; Fan, Zhichao; Chen, Yongdong; Nie, Defu; Wu, Qiaoguo
Highlights: 3D CFD simulation of supercritical LNG heat transfer in an IFV. Reasonable accuracy of DPM for supercritical LNG heat transfer in a tube bundle. Noticeable effect of LNG composition on thermal performance of the vaporizer. Abstract: A three-dimensional transient computational fluid dynamics (CFD) model has been established for the simulations of supercritical heat transfer of real liquefied natural gas (LNG) mixture in a single tube and a tube bundle of an intermediate fluid vaporizer (IFV). The influence of chemical composition of LNG on the thermal performance has been analyzed. The results have also been compared with those obtained from the one-dimensional steady-state calculations using the distributed parameter model (DPM). It is found that the current DPM approach can give reasonable prediction accuracy for the thermal performance in the tube bundle but unsatisfactory prediction accuracy for that in a single tube as compared with the corresponding CFD data. As benchmarked against pure methane, the vaporization of an LNG containing about 90% (mole fraction) of methane would lead to an absolute deviation of 5.5 K in the outlet NG temperature and a maximum relative deviation of 11.4% in the tube side HTC in a bundle of about 816 U tubes at the inlet pressure of 12 MPa and mass flux of 200 kg·m −2 ·s −1 . It is concluded that the influence of LNG composition on the thermal performance should be taken into consideration in order to obtain an economic and reliable design of an IFV.